COMPATIBILIZAÇÃO DE PROJETO DE INSTALAÇÕES: UM ESTUDO COMPARATIVO ENTRE O MÉTODO TRADICIONAL (2D) E A FERRAMENTA BIM - Figueiredo, Luana; Mariano, Litiele; Resende, Lucas; Campos Neto, Lúcio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present work deals with a comparative study between software of 2D drawings and a BIM tool as methods in the compatibility of projects of hydraulic and electrical installations. The study is a comparison between the traditional (2D) method, which is a more common practice in project development, which is already obsolete, since it may be baffled by some errors that appear in three-dimensional views, and BIM, which consists of parameterizing the elements of a building with the information, is an integral part of a three-dimensional project, demonstrating that it is the most efficient. It also presents fundamentals and tools of traditional methods and BIM, with their characteristics, difficulties in making compatible with the traditional method (2D) and as disadvantages and advantages of compatible projects using a tool BIM.